IMPLEMENTASI UNDANG-UNDANG NOMOR 13 TAHUN 2008 TENTANG PENYELENGGARAAN IBADAH HAJI - Refenza, Renoctha (UIN Fatmawati Sukarno Bengkulu, 2022)
Abstract: The purpose of this study was to analyze: First, the working relationship between the Regional Government of Seluma District and the Ministry of Religion of Seluma District in organizing the Hajj. Second, the factors that influence the working relationship in the implementation of the pilgrimage in Seluma District. This type of research is qualitative research. Data collection uses interview, observation and documentation techniques. Data analysis techniques use data reduction, data display and conclusion drawing.This study concludes that: First, the working relationship between the District Government of Seluma and the Ministry of Religious Affairs of Seluma Regency has been well established. Working relationships indicate that there is an important role for the Regional Government and the Ministry of Religious Affairs in succeeding the implementation of Hajj in Seluma District. The parties are responsible for the implementation of Hajj in accordance with their field of duty. Ministry of Religious Affairs Seluma District plays an important role in the matter of fostering the people, education and socialization in hajinya. Second, the factors that affect the working relationship between the Government of Seluma District and the Ministry of Religious Affairs of Seluma Regency in performing the Hajj are: First, Supporting factor is the interest of the people of Seluma Regency who are high to be able to perform the pilgrimage, the knowledge of the society about the position of Hajj in Islam, the ability of the society economically, the synergy between the district government and the Ministry of Religious Affairs in the management of Hajj. Secondly, the inhibiting factor is the wide area of Seluma Regency up to the hinterland, making it difficult for the implementation of socialization and guidance of the pilgrims to pilgrims, still lack of specialized personnel who administer on-line hajj registration and limited internet network in Seluma District. Keywords: Law Number 13 of 2008, Employment Relations, Implementation of Hajj Abstrak: Tujuan penelitian ini adalah untuk menganalisis: Pertama, hubungan kerja antara Pemerintah Daerah Kabupaten Seluma dengan Kementerian Agama Kabupaten Seluma dalam. penyelenggaraan haji Kedua,faktor yang mempengaruhi hubungan kerja dalam. penyelenggaraan ibadah haji di Kabupaten Seluma. Jenis penelitian ini adalah penelitian kualitatif .Pengumpulan data menggunakan teknik wawancara, observasi dan dokumentasi. Teknik analisa data menggunakan reduksi data, display data dan penarikan kesimpulan. Penelitian ini menyimpulkan bahwa : Pertama, hubungan kerja antara Pemerintah Kabupaten Seluma dan Kementerian Agama Kabupaten Seluma telah terjalin dengan baik. Hubungan kerja menunjukan bahwa ada peran penting bagi Pemerintah Daerah dan Kementerian Agama dalam mensukseskan penyelenggaraan haji di Kabupaten Seluma. Pihak-pihak tersebut bertanggung jawab terhadap pelaksanaan penyelenggaraan haji sesuai dengan bidang tugasnya. Kementerian Agama Kabupaten Seluma berperan penting dalam soal pembinaan umat, pendidikan dan sosialisasi dalam hajinya. Kedua, faktor yang mempengaruhi hubungan kerjaantara Pemerintah Kabupaten Seluma dan Kementerian Agama Kabupaten Seluma dalam penyelenggaraan haji adalah Pertma, factor Pendukung yaitu minat masyarakat Kabupaten Seluma yang tinggi untuk dapat menunaikan ibadah haji, pengetahuan masyarakat tentang kedudukan haji dalam Islam, kemampuan masyarakat secara ekonomi, adanya sinergi antara pemerintah kabupaten dan pihak Kemenagalam pengelolaan haji. Kedua, faktor Penghambat yaitu wilayah Kabupaten Seluma yang luas hingga ke daerah pedalaman sehingga menyulitkan pelaksanaan sosialisasi dan pembinaan manasik kepada jamaah calon haji, masih kurangnya tenaga khusus yang mengelola pendaftaran haji secara on-line dan terbatasnya jaringan internet di Kabupaten Seluma. Kata Kunci: UU Nomor 13 tahun 2008, Hubungan Kerja, Penyelenggaraan Haji